Evidence supporting the enhanced efficacy of pentavalent antimonials with adjuvant therapy for cutaneous leishmaniasis: a systematic review and meta‐analysis. (3rd July 2020) - Husein‐ElAhmed, H.; Gieler, U.; Steinhoff, M.
Abstract: Cutaneous leishmaniasis (CL) is one of the major neglected disease worldwide. Although many drugs have been used, the pentavalent antimonials (PA) remain as the first‐line choice despite their toxicity and limited efficacy. The combination of two drugs has risen as a potential alternative to increase the cure rate while lowering the side‐effects caused by pentavalent antimonials (PA). The objective of this study was to critically review and appraise the potential synergism of the adjuvant therapies of PA with other drugs/interventions previously used in the literature. We carried out a search of literature from PubMed, MEDLINE, Embase, Cochrane and clinicaltrials.gov. Articles that described a two‐arm or three‐arm design in which one of the arms consisted in a combination of a drug/intervention with intralesional or systemic PA were selected. The primary outcome was proportion of complete clearance of the lesions defined as complete re‐epithelization and/or negative direct smear. Our literature search identified 554 references. Thirty‐one records with a total sample size of 2668 participants met the eligibility criteria. The studies investigated the association of PA with the following: cryotherapy (five studies), allopurinol, imiquimod, pentoxifylline (four studies each), trichloroacetic acid 50% (three studies) and other additional interventions (eleven studies). Overall, the combined therapy of PA with a supplementary intervention was superior to PA monotherapy (RR: 1.23 95% CI: 1.11–1.35, I 2 = 64%). In association with PA, the comparator‐specific stratified analysis showed that cryotherapy (RR: 1.50 95% CI: 1.25–1.81, I 2 = 57%) and allopurinol (RR: 1.70 95% CI: 1.37–2.12, I 2 = 28%) were superior to PA in monotherapy. On the contrary, the combined therapy with imiquimod (RR: 1.08 95% CI: 0.88–1.32, I 2 = 40%) and pentoxifylline (RR: 1.14 95% CI: 0.94–1.40, I 2 = 41%) revealed a non‐significant result. The application of TCA along with PA did not show significant differences in the clearance rate, although it was close to it (RR: 1.31 95% CI: 0.99–1.73, I 2 = 84%). The present work represents an attempt to find new and reliable treatment modalities to enhance the efficacy based on the adjuvant therapy of pre‐existing drugs/interventions with PA. According to our results, the combination of allopurinol‐PA is the most effective adjuvant therapy. The application of cryotherapy and TCA stand as useful and encouraging supplementary interventions. The combination of imiquimod‐PA and pentoxifylline adds no additional benefit. The results of this work may be helpful in devising and modifying the current guidelines for CL which face major remaining evidence gaps. Triple therapies consisting in cryotherapy‐PA‐TCA or allopurinol‐PA‐cryotherapy or allopurinol‐PA‐TCA can represent promising treatments yet to be confirmed in future trials.